2023
DOI: 10.1111/dmcn.15572
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Cochrane systematic reviews for rehabilitation interventions in individuals with cerebral palsy: A mapping synthesis

Abstract: AimThis overview of Cochrane systematic reviews (CSRs) reports on current evidence on the effectiveness of rehabilitation interventions for individuals with cerebral palsy (CP) and the quality of the evidence.MethodFollowing the inclusion criteria defined by the World Health Organization, all CSRs tagged in the Cochrane Rehabilitation database that were relevant for individuals with CP were included. A mapping synthesis was used to group outcomes and comparisons of included CSRs indicating the effect of rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…A second set of lessons came to Cochrane Rehabilitation while working with the WHO to identify the evidence to produce the Package of Interventions for Rehabilitation, 8 a tool offered to countries as the minimum rehabilitation services needed to provide to their citizens. One of the main results, published in a series of Overviews of Cochrane Reviews, 9 - 13 was that the evidence from randomised controlled trials (RCTs) was scarce in quantity and often low in quality. This surprising result showed that RCTs currently do not and in all likelihood cannot answer the range of research questions arising from practice information needs to provide all the evidence we need to treat our patients.…”
Section: The 5 Th Cochrane Rehabilitation Methodol...mentioning
confidence: 99%
“…A second set of lessons came to Cochrane Rehabilitation while working with the WHO to identify the evidence to produce the Package of Interventions for Rehabilitation, 8 a tool offered to countries as the minimum rehabilitation services needed to provide to their citizens. One of the main results, published in a series of Overviews of Cochrane Reviews, 9 - 13 was that the evidence from randomised controlled trials (RCTs) was scarce in quantity and often low in quality. This surprising result showed that RCTs currently do not and in all likelihood cannot answer the range of research questions arising from practice information needs to provide all the evidence we need to treat our patients.…”
Section: The 5 Th Cochrane Rehabilitation Methodol...mentioning
confidence: 99%
“…As for previously published paper [ 16 ], we extracted data about each reported outcome related to an intervention from Table of Findings of each CSR. We extracted GRADE judgments within the CSRs when reported; otherwise, we judged the quality of evidence for the primary outcome, using the standard GRADE approach [ 20 , 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…In previous publications, we detailed the methodology [16] that follows what was established and published by the WHO Rehabilitation Programme and Cochrane Rehabilitation [2] under the guidance of the WHO's guideline review committee. We performed an overview of CSRs reported following the Preferred Reporting Items for Systematic Reviews and Meta-analysis (PRISMA 2020 statement) [17] and registered on OSF Registries (https://doi.org/10.17605/OSF.IO/9QKYB (accessed on 28 March 2024)).…”
Section: Methodsmentioning
confidence: 99%
“…AMSTAR 2 is a 16-item, domain-based instrument meant to critically appraise systematic reviews of randomized controlled trials [ 18 ]. Seven domains of the instrument are considered critical to rate the methodological quality of the study, namely protocol registration before commencement of the review, adequacy of the literature search, justification for excluding individual studies, risk of bias from individual studies included in the review, appropriateness of meta-analytical methods, consideration of risk of bias when interpreting the results of the review and assessment of the likely impact of publication bias [ 18 , 19 ]. The identification of weaknesses in these critical domains allows one to correctly interpret the information provided by the systematic reviews, and provides four classification levels: ‘high quality’, ‘moderate quality’, ‘low quality’ and ‘critically low quality’ evidence [ 18 ].…”
Section: Methodsmentioning
confidence: 99%